Managing Diversity as A Foundation of Religious Tolerance: A Study in Sidoasri Village, The Regency of Malang - Dhanny Septimawan Sutopo (Bina Nusantara University, 2016)
Amongst other things, Indonesian history was rife with religious conflicts. Religious differences had thus far been factored in the causes of intolerance amongst believers of different religions. This study examined how religious tolerance that was established in Sidoasri village where Christians and Muslims were living together. This research used a qualitative descriptive method, where it would describe and explain data from the subject research on the form of religious tolerance in Sidoasri village. The results of this research show that religious tolerance is always built through the long process by way of mediating various past conflicts. Religious dogma has never been a cause of intolerance. Social, cultural, political, and economic factors are decisive in founding religious tolerance.